Politik Identitas Gender dalam Pemilihan Kepala Daerah Tahun 2020 di Kota Makassar - Yakub, Andi Amirah Humairah; Tamma, Sukri; Yunus, Ariana (Palita: Journal of Social Religion Research, 2024)
Identity politics in democracy continues to be a topic of discussion, particularly regarding issues related to gender, religion, language, race, and ethnicity. These factors are often studied in the context of political identity during election periods, such as during the 2020 election in the city of Makassar. , Fatmawati Rusdi is the only female contestant in the Makassar City Election and makes history for women in the government seat for the next five years. The purpose is to describe how gender identity politics became a strategy for winning the 2020 regional elections in Makassar City. The research method used is a qualitative descriptive research method with a literature study and observation approach. The research results explain the gender identity politics in the Makassar City election, where Fatmawati Rusdi became the first female deputy mayor in Makassar City, the only woman to compete in the Makassar City election, Fatmawati Rusdi applied direct communication (door-to-door) with the community instead of image building in the media. Conclusion from this research, the involvement of women in local elections happened almost throughout Indonesia, especially in the city of Makassar, starting with the 2020 local elections where a woman was elected as the Deputy Mayor of Makassar. To win, Fatmawati Rusdi used the right strategy to gain the support of the mothers of the taklim councils in the alleys, one of the female sports communities often cycling, which greatly helped in the approach of campaigning and delivering the programs to be done when in office